2019
DOI: 10.18510/hssr.2019.7149
|View full text |Cite
|
Sign up to set email alerts
|

Self-Concept, Perception of the Learning Environment and Employability: A Study of Vocational High School Students in Prambanan Yogyakarta, Indonesia

Abstract: Purpose: This study aimed to empirically examine the role of self-concept and perception of the learning environment on the employability of students who attend Muhammadiyah Vocational High School Prambanan Yogyakarta, Indonesia. Methodology: The subjects of this study were 132 Grade XII students of Muhammadiyah Vocational High School Prambanan Yogyakarta, Indonesia. The sampling in this study was randomized using cluster random sampling technique. Data was collected using the self-concept scale, percept… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 27 publications
0
5
0
1
Order By: Relevance
“…The findings of this study are different from previous studies. The results of previous studies that examined workreadiness found that factors related to workreadiness were self-concept and perception of the learning environment [49], entrepreneur intention and responsibility [50,51], academic achievement and self-concept [29], motivation to learn and social support [11]. This research is expected to develop the results of previous research to be more comprehensive in uncovering the problems of student work readiness.…”
Section: Multiple Linear Regression Analysismentioning
confidence: 90%
“…The findings of this study are different from previous studies. The results of previous studies that examined workreadiness found that factors related to workreadiness were self-concept and perception of the learning environment [49], entrepreneur intention and responsibility [50,51], academic achievement and self-concept [29], motivation to learn and social support [11]. This research is expected to develop the results of previous research to be more comprehensive in uncovering the problems of student work readiness.…”
Section: Multiple Linear Regression Analysismentioning
confidence: 90%
“…Factors that influence employability include soft-skill factors, problem-solving skill factors, internship  ISSN: 2089-9823 experience factors, special skills factors, and learning achievement factors [35]. Some researchers add other factors that affect employability, namely: learning achievement, self-concept [36], motivation to learn, social support [37], career management practices, work experience, training, education [38], autonomy, discipline [39], self-concept, and perceptions of the learning environment [40]. Motivation to learn is a factor that can facilitate the interests and needs of individuals to enter the workforce [41].…”
Section: Hypothesis Testingmentioning
confidence: 99%
“…Pelatihan pengembangan minat berwirausaha telah mampu mengembangkan konsep diri peserta didik agar memiliki keyakinan akan usahanya dan keberhasilan dalam kerja bukan merupakan keberuntungan dengan konsep diri yang kuat dan lingkungan belajar yang baik, kematangan mental siswa untuk berwirausaha setelah tamat nanti menjadi lebih kuat. konsep diri dan lingkungan belajar berperan penting dalam mempersiapkan siswa memperoleh pengetahuan, keterampilan, pemahaman, dan kepribadian di lingkungan Sekolah Menengah Kejuruan, untuk kemudian diterapkan di dunia kerja setelah lulus (Tentama & Jayanti, 2019). Siswa juga mengalami peningkatan pengetahuan dan kemampuan di bidang wirausaha.…”
Section: Hasil Dan Pembahasanunclassified